Implementasi Budaya Religius Melalui Morning Spiritual Terhadap Kedisiplinan Siswa SMK Batik 1 Surakarta - Muhammad Mirza Nurrahman; Dartim Dartim (Jayapangus Press, 2026)
Strengthening discipline character in vocational high schools requires habituation strategies that go beyond formal instructional approaches. This study aims to analyze the effectiveness of the Morning Spiritual program in shaping students' religious and disciplinary character at SMK Batik 1 Surakarta. Using a descriptive qualitative method with Miles and Huberman's interactive analysis, this study found that: (1) The spiritual approach through Dhuha Prayer and Asmaul Husna is more effective in touching students' intrinsic motivation compared to ceremonial approaches; (2) This program contributes concretely to students' work readiness, particularly in time management aspects; (3) Implementation obstacles include sanitation limitations and student mobilization resistance; (4) Solutive strategies are implemented through the role of Homeroom Teachers (Wali Kelas) as 'Character Managers' to ensure collective discipline. The study concludes that the success of school culture depends on the synergy between physical facility support and teacher managerial collaboration.